The gist and significance of wrist work in the old Polish fencing sabre based on selected techniques of cuts and thrusts - Leonard Marynowski (Universidad de León, 2019)
The aim of this study was to determine the essence and importance of wrist movements for the old Polish sabre fencing. Analysis of available writings, work with old Polish fencing students in the years 2009 - 2019, empirical interpretation of the described techniques. The analysis of available writings, the work with old Polish fencing students in the years 2009 - 2019, and empirical interpretation of the described techniques were used. Results showed that wrist work was essential for the execution of a number of historical techniques. It allowed to gain control over the opponent's blade and prevail in the clash. Further research on old Polish fencing is necessary.